Pharmacokinetics and antiviral activity of cabotegravir and rilpivirine in cerebrospinal fluid following long-acting injectable administration in HIV-infected adults. (24th December 2019) - Letendre, Scott L; Mills, Anthony; Hagins, Debbie; Swindells, Susan; Felizarta, Franco; Devente, Jerome; Bettacchi, Christopher; Lou, Yu; Ford, Susan; Sutton, Kenneth; Shaik, Jafar Sadik; Crauwels, Herta; et al.
Abstract: Background: Long-acting (LA) formulations of cabotegravir, an HIV integrase inhibitor, and rilpivirine, an NNRTI, are in development as monthly or 2 monthly intramuscular (IM) injections for maintenance of virological suppression. Objectives: To evaluate cabotegravir and rilpivirine CSF distribution and HIV-1 RNA suppression in plasma and CSF in HIV-infected adults participating in a substudy of the Phase 2b LATTE-2 study (NCT02120352). Methods: Eighteen participants receiving cabotegravir LA 400 mg + rilpivirine LA 600 mg IM [every 4 weeks (Q4W), n = 3] or cabotegravir LA 600 mg + rilpivirine LA 900 mg IM [every 8 weeks (Q8W), n = 15] with plasma HIV-1 RNA <50 copies/mL enrolled. Paired steady-state CSF and plasma concentrations were evaluable in 16 participants obtained 7 (±3) days after an injection visit. HIV-1 RNA in CSF and plasma were assessed contemporaneously using commercial assays. Results: Median total CSF concentrations in Q4W and Q8W groups, respectively, were 0.011 μg/mL and 0.013 μg/mL for cabotegravir (0.30% and 0.34% of the paired plasma concentrations) and 1.84 ng/mL and 1.67 ng/mL for rilpivirine (1.07% and 1.32% of paired plasma concentrations). Cabotegravir and rilpivirine total CSF concentrations exceeded their respective in vitro EC50 for WT HIV-1 (0.10 ng/mL and 0.27 ng/mL, respectively). All 16 participants had HIV-1 RNA <50 copies/mL in plasma and CSF, and 15 of 16 participants had HIV-1 RNA <2 copies/mL in CSF. Conclusions: A dual regimen of cabotegravir LA and rilpivirine LA achieved therapeutic concentrations in the CSF resulting in effective virological control in CSF.